Do Earnings by College Major Affect Graduate Migration? - John V. Winters (Institute for the Study of Labor (IZA), 2015)
College graduates are considerably more mobile than non-graduates, and previous literature suggests that the difference is at least partially attributable to college graduates being more responsive to employment opportunities in other areas. However, there exist considerable differences in migration rates by college major that have gone largely unexplained. This paper uses microdata from the American Community Survey to examine how the migration decisions of young college graduates are affected by earnings in their college major. Results indicate that higher major-specific earnings in an individual's state of birth reduce out-migration suggesting that college graduates are attracted toward areas that especially reward the specific type of human capital that they possess.
Keywords: J24; J61; R23; 330; graduate migration; college major; college graduates; human capital